Classification of Chinese Traditional Jade Carvings - Ma, Huafei; Theppituck, Tatiya (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The art of jade carving is a vital carrier of Chinese cultural values and aesthetic ideals. However, systematic classification research on traditional Chinese jade carvings remains limited. This study aims to construct a comprehensive classification framework from the perspectives of modeling, craftsmanship, and themes. Materials and Methods: A multi-method approach was adopted, combining literature review, physical artifact analysis, expert interviews, and market research. These methods ensured a thorough understanding of the artistic diversity and evolving practices of jade carving. Results: The study developed a detailed three-dimensional classification system for traditional Chinese jade carvings. It revealed four modeling types, multiple craftsmanship techniques, and major thematic categories, showcasing the rich cultural connotations and technical innovation of jade art. Conclusion: By systematically classifying traditional Chinese jade carvings, this research deepens the understanding of their artistic value and cultural significance. It provides theoretical support for the preservation, education, and creative development of jade carving in contemporary contexts.